Mineral deposits of public importance (MDOPi) in relation to the project of the national mineral policy of Poland - Galos, Krzysztof (2018)
The functioning of European economies and societies requires a stable and sustainable supply of mineral resources. For 10 years now EU has been developing raw materials initiative to secure European minerals supply. In many cases, areas with known or hypothetic mineral resources, are not sufficiently valued by society and authorities, remain unprotected and face competing land uses with the risk of becoming sterilized. MINATURA 2020 project was born out of a need to develop a harmonised framework which allow a common way of identifying “mineral deposits of public importance” (MDoPI) and their safeguarding via land use planning. The project has left a useful set of guidelines and proposals how to advance on the creation of a European network of MDoPIs to avoid sterilization of “deposits worth safeguarding”. In Poland, the need for legal protection of mineral deposits has been discussed intensively in recent years. Various proposals aimed at better system of mineral deposits safeguarding, especially those which should be recognized as of public importance, have been proposed. However, until now only a few coal deposits were recognized as strategic. Currently, the Polish National Mineral Policy is under preparation. Its overriding objective is to provide access to the necessary minerals, also in the longterm perspective. It assumes among others activities aimed at protection of mineral deposits regarding land use planning system. Paper presents scope and general results of MINATURA2020 project, with details on MINATU-RA2020 methodology implementation in Poland, Project of the Polish National Mineral Policy with its objectives and key pillars, position of MDoPIs in this Project, and – finally – expected future steps related to MDoPI safeguarding in EU and in Poland.